Optimizing Crime Pattern Analysis in India: The Role of Ensemble Learning in Predictive Policing - Pallavi (My University, 2024)
This research investigates the application of regression models and advanced machine-learning techniques to forecast crime patterns in India, thereby enhancing public safety. By analyzing datasets encapsulating geographic and temporal variables, the study demonstrates the robustness of ensemble models in predicting crime rates effectively. A meticulous approach to outlier removal, data transformation, and model evaluation was adopted to optimize the accuracy and reliability of the predictive models. Historical crime data, incorporating features such as location, time, type of crime, and socioeconomic factors, was utilized to identify significant predictors of crime occurrences and capture complex, non-linear relationships within the data. The study extensively employs stacking-based ensemble learning methods to improve prediction outcomes over single-model approaches. Results confirm that integrating machine learning techniques enhances the precision of crime forecasts and sets a new benchmark for predictive accuracy, thus advancing in predictive analytics and offering promising directions for proactive crime prevention. By proactively identifying potential crime hotspots, the proposed model can aid law enforcement in optimizing resource allocation, focusing on high risk areas, and potentially deterring criminal activity. Furthermore, the study highlights future advancements in integrating new data sources, such as social media trends and real-time urban data, to refine prediction models. Ultimately, this research aims to demonstrate how machine learning can be a valuable tool in crime prevention strategies, fostering safer communities while emphasizing the importance of responsible and transparent implementation of these technologies in law enforcement practices.
Keywords: forecast crime patterns; forecast; crime; Ensemble Learning